2018
DOI: 10.1103/physrevd.98.084036
|View full text |Cite
|
Sign up to set email alerts
|

Spin orientations of merging black holes formed from the evolution of stellar binaries

Abstract: We study the expected spin misalignments of merging binary black holes formed in isolation by combining state-of-the-art population-synthesis models with efficient post-Newtonian evolutions, thus tracking sources from stellar formation to gravitational-wave detection. We present extensive predictions of the properties of sources detectable by both current and future interferometers. We account for the fact that detectors are more sensitive to spinning black-hole binaries with suitable spin orientations and fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
262
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 230 publications
(271 citation statements)
references
References 106 publications
(223 reference statements)
6
262
3
Order By: Relevance
“…[69] for nonspinning BHs (Refs. [62,70,71] showed that spins have a marginal effect on p det unless strong alignment is present, which is not our case). The probability p det corresponds to the (unnormalized) detection rate, allowing us to estimate detector selection effects on the GW events resulting from our model.…”
Section: The Modelmentioning
confidence: 64%
“…[69] for nonspinning BHs (Refs. [62,70,71] showed that spins have a marginal effect on p det unless strong alignment is present, which is not our case). The probability p det corresponds to the (unnormalized) detection rate, allowing us to estimate detector selection effects on the GW events resulting from our model.…”
Section: The Modelmentioning
confidence: 64%
“…Gravitational-wave astronomy offered new possibilities of direct measurement of BH spins in coalescing binary BHs. The current LIGO/Virgo results [16] suggest a fairly narrow effective BH spin distribution around zero χ eff ∼ 0, which can be used to understand the origin of coalescing binary BH with masses 10-60 M [73,74].…”
Section: Resultsmentioning
confidence: 99%
“…Combining high-and low-frequency GW detections of the same source can also help identify the astrophysical channel responsible of BBH formations. Different scenarios in fact result in different masses, mass ratios, spins and eccentricity distributions of the detected sources [12][13][14][15][16][17]. Because of the GW circularization, BBHs may have small eccentricity in the LIGO/Virgo band, regardless of their formation channels.…”
Section: Introductionmentioning
confidence: 99%